Introduction to psychology and counseling Christian perspectives and applications - Meier, Paul D.; Minirth, Frank B.; Wichern, Frank B.; Ratcliff, Donald E. (Grand Rapids, MI Baker, 1991)
Includes bibliographical references and indexes.
Rev. ed. of : Introduction to psychology and counselling / Paul D. Meier, 1982
Keywords: Pastoral counselling; Psychology and religion